ANALYSIS OF THE EFFECTIVENESS OF IMPLEMENTING ACTIVE METHODOLOGIES IN HIGHER EDUCATION: AN INTEGRATIVE REVIEW ON THE CASE OF HISTOLOGY: análise da eficácia da implementação de metodologias ativas no ensino superior: uma revisão integrativa sobre o caso da histologia - Juliana Machado Amorim; Saulo felipe costa; Carolina Santiago Silveira Polaro Araújo; Vilma Felipe Costa de Melo; Cletiane Medeiros Costa de Araújo; Frederico Augusto Polaro Araújo Filho (Revista de Ciências da Saúde Nova Esperança, 2025)
Histology teaching traditionally uses expository methods, but active learning methodologies are being introduced to promote more meaningful and contextualized learning through a deeper understanding of concepts, more lasting knowledge retention, and stimulating the development of cognitive skills. The objective of this integrative review was to evaluate the effectiveness of implementing active learning methodologies in histology teaching. The integrative review was conducted through an extensive search of the Capes Periodicos and Lilacs databases, including articles published in English and Portuguese between 2020 and 2024, using combinations of controlled descriptors. A total of 18 articles were found for final selection, with 11 articles included and 7 excluded after analysis. The results indicated that active teaching methodologies contribute to greater knowledge retention and improved academic performance. The review suggests that implementation improves academic performance and student motivation, although more experimental studies are needed to confirm these findings in varied contexts.